Synthesis and Evaluation of Antibacterial and Antiinflammatory Activity of 7-Alkyl/Aryl amino-6-fluoro- 2-phenyl Carboxamido-1,3-benzothiazoles - SARKAR, SIBAJI; YUNUS PASHA, T.; SHIVAKUMAR, B.; MALLA REDDY, V. (Asian Journal of Chemistry, 2010)
Substituted-1,3-benzothiazole is synthesized by 2-amino- 7-chloro-6-fluorobenzothiazoles with aroyl chloride and later on obtained compound were refluxed in equimolecular with various substituted amines. These were characterized by spectral data and were screened for biological and pharmacological activity.